2000
DOI: 10.1016/s0006-3495(00)76502-7
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Dependent Recruitment of di22:6-PC by a G Protein-Coupled Receptor into Lateral Domains

Abstract: Bovine rhodopsin was reconstituted into mixtures of didocosahexaenoylphosphatidylcholine (di22:6-PC), dipalmitoylphosphatidylcholine (di16:0-PC), sn-1-palmitoyl-sn-2-docosahexaenoylphosphatidylcholine (16:0, 22:6-PC) and cholesterol. Rhodopsin denaturation was examined by using high-sensitivity differential scanning calorimetry. The unfolding temperature was increased at lower levels of lipid unsaturation, but the highest temperature was detected for native disk membranes: di22:6-PC < 16:0,22:6-PC < di16:0,18:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 51 publications
8
83
0
Order By: Relevance
“…A correlation between lipid organization in the context of a membrane raft, phototransduction, and lipid and protein sorting is in the early stages of characterization. Recent model membrane studies suggest that cholesterol is necessary for the recruitment of polyunsaturated fatty acids by rhodopsin into membrane microdomains (25). Similar studies also demonstrated the requirement for specific lipids in the activation process of rhodopsin (26 -28), in transducin binding (29), and in phosphodiesterase activation (30).…”
mentioning
confidence: 85%
“…A correlation between lipid organization in the context of a membrane raft, phototransduction, and lipid and protein sorting is in the early stages of characterization. Recent model membrane studies suggest that cholesterol is necessary for the recruitment of polyunsaturated fatty acids by rhodopsin into membrane microdomains (25). Similar studies also demonstrated the requirement for specific lipids in the activation process of rhodopsin (26 -28), in transducin binding (29), and in phosphodiesterase activation (30).…”
mentioning
confidence: 85%
“…The ability of the lipids and rhodopsin to organize into complex lateral domains has also been investigated by Litman and colleagues. Their studies showed that there is a cholesterol-dependent recruitment of di22:6-PC by rhodopsin into lateral domains of the disk bilayer [106]. The cluster of rhodopsin and the lipids that formed this domain exceeded two adjacent lipid layers.…”
Section: Organization Of Cholesterol In Disk Membranesmentioning
confidence: 99%
“…Even with so much new information, the connection between events of cell biology and particular lipid compositions-a kind of "lipid role assignment"-can be made in but a few cases. These exceptions include the phosphoinositide binding of particular proteins to the plasma membrane inner leaflet (McLaughlin and Murray 2005) and polyunsaturated acyl chains of lipids in the retinal rod, which are needed for full activity of rhodopsin (Polozova and Litman 2000). More information is known about plasma membranes than about any other cell membranes, making the plasma membrane a starting point for thinking about lipid roles in mammalian cell membranes.…”
Section: Lipids Found In Cell Membranesmentioning
confidence: 99%